Evaluation of Education as a Tool for Improving Learning Quality to Empower the Younger Generation - Husna, Faiqatul (SALAM: Jurnal Sosial dan Budaya Syar-i, 2025)
Quality education is key to empowering the younger generation and preparing them to face future challenges. However, current educational evaluation practices often prove ineffective in enhancing the quality of learning. Therefore, this research was conducted to explore the role of educational evaluation as a tool for improving learning quality. This study aims to identify the effectiveness of evaluation methods applied in schools and how they can enhance student engagement and learning outcomes. This research employs a mixed-methods approach, combining qualitative and quantitative methods. Data were collected through interviews with educators and students, classroom observations, and curriculum document analysis. The research population consists of educators and students from several secondary schools in Aceh.Principal Results: The findings indicate that many educators feel that the evaluation methods currently in use are not fully effective. Students also desire more varied and interactive evaluation methods. Additionally, there is a gap between evaluation results and curriculum improvement that needs to be addressed. The study concludes that effective educational evaluation must actively involve students and be integrated with the curriculum. Thus, evaluation should not only serve as a measurement tool but also as a means to enhance the quality of learning. This research provides new insights into the importance of student involvement in evaluation and the need for training for educators to implement better evaluation methods. The findings are expected to serve as a reference for policymakers and educators in designing more effective evaluation strategies.Keywords: Educational evaluation; learning quality; student engagement; evaluation methods; education